Human clinical trial of plasmapheresis effects on biomarkers of aging (efficacy and safety trial) - Borsky, Pavel; Holmannova, Drahomira; Parova, Helena; Horvath, Steve; Sramek, Petr; Brooke, Robert T.; Milciute, Milda; Gordevicius, Juozas; Fiala, Zdenek; Andrys, Ctirad; Kremlacek, Jan; Rehacek, Vit; et al. (Scientific reports, 2025)
Plasmapheresis is a medical procedure that separates plasma from blood cells, potentially removing pro-aging factors from circulation. Some studies suggest it may have rejuvenating effects by altering biomarkers of aging, but evidence on its impact on epigenetic aging in humans is limited. This study aimed to assess whether plasmapheresis without volume replacement with young plasma or albumin affects epigenetic age and other biomarkers in healthy adults. An automatic plasma collection system, the Haemonetics PCS2, was used for plasmapheresis. Healthy blood donors were divided into two groups using stratified randomization in a cross-over study with subjects undergoing either 8 plasmaphereses (8 pp) or 4 plasmaphereses (4 pp) for an 18-week period, with a minimum interval between plasmaphereses of 2 weeks (14 days). Samples were tested for biochemical, hematological analyses and epigenetic clocks. We documented the alteration in serum minerals, decreased serum lipids, mainly total cholesterol, non-HDL, triglycerides, apolipoprotein A levels, total proteins and albumin. Among hematologic parameters, we found an increase in Red Cell Distribution Width (RDW) and Mean Corpuscular Hemoglobin Concentration (MCHC). No significant epigenetic rejuvenation was observed based on epigenetic clock measurements. Instead, plasmapheresis was associated with increases in DNAmGrimAge, the Hannum clock, and the Dunedin Pace of Aging. Plasmapheresis can rapidly change the levels of pro-inflammatory and other pro-aging molecules in the circulation. However, the selected protocol has not provided conclusive data supporting benefits. Based on epigenetic clock parameters, it may accelerate epigenetic aging. More research into the long-term safety of this specific protocol is needed.